UNDERSTANDING THE PRINCIPLES OF DIFFERENTIATE LEARNING: OPTIMIZING THE POTENTIAL OF EVERY STUDENT IN CLASS - Ernati; Siti Mayang Sari; Akmaluddin; Lili Kasmini (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
There are differences in each individual student, so different learning is needed to meet different learning needs. The purpose of this study is to explain differentiation learning in optimizing students' potential. This study uses the historical research method with data sources in the form of research journals that have been published and have relevance to the title of this article. Literature study data collection techniques by searching online related to relevant journals. Data analysis was carried out in a qualitative descriptive manner. Differentiated learning is an attempt to condition the learning process in the classroom so that it meets the individual learning needs of each student. The teacher must adapt the needs of students to the learning process. There are three strategies for implementing differentiated learning, namely content differentiation, process differentiation and product differentiation. These three strategies must be adapted to aspects of learning readiness, interests and student learning profiles. The application of differentiated learning results in an increase in student learning activities, both activeness and the level of student participation during the learning process. Some of the obstacles to the implementation of differentiated learning are when grouping students according to learning interests, profiles and learning readiness, the application of content differentiation in learning, and in the assessment process, and time management in the learning product projects that are made